ROAD INFRASTRUCTURE DEVELOPMENT IN BUKIT PERMATA VILLAGE, KAUBUN DISTRICT, EAST KUTAI REGENCY - Fika Romantika; Hariati Hariati (Universitas Negeri Makassar, 2026)
Road infrastructure development in rural areas is an important aspect because it directly affects accessibility, community mobility, distribution of agricultural products, and improvement of rural community welfare. This study aims to describe and analyze road infrastructure development in Bukit Permata Village, Kaubun District, East Kutai Regency, and to identify the supporting and inhibiting factors in its implementation.This study used a descriptive qualitative approach. The research focused on three main stages of village road infrastructure development, namely planning, implementation, and supervision or monitoring. Data were collected through observation, interviews, and documentation. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldana. The results show that road infrastructure development in Bukit Permata Village has been implemented properly through the stages of planning, implementation, and supervision or monitoring. However, some implementation processes have not run optimally because development has not been fully distributed. The implementation also still faces several obstacles, including geographical conditions, limited labor, unavailable construction materials, and budget constraints. Therefore, it can be concluded that road infrastructure development in Bukit Permata Village has provided benefits for the community by improving accessibility and supporting village economic activities. However, equitable development, stronger supervision, and better planning still need to be improved so that road infrastructure development can run more effectively, evenly, and sustainably.